Spatial warping techniques for unstructured transmission line modelling method - Altinozen, Ekrem (2023)
Flexible, foldable, and wearable antennas and interconnects play an indispensable role in the rise of wearable computing and wireless communications across many application areas. However, wearable components experience inevitable mechanical deformation, that can cause frequency shifting, performance detuning and component degradation making wireless data transmission and power transmission capabilities are limited. Thus, it is important to assess to what degree antenna and interconnect performance can be tolerant to in-situ deformations that can take the form of bending, crumpling and twisting and combinations of these effects. However, generating geometries of arbitrary antenna deformations such as bending, crumpling, and twisting, that can be processed by standard electromagnetic software is a major challenge that significantly complicates full assessment of in-situ antenna performance. Constructive Solid Geometry (CSG) methods of generating geometries is difficult to robustly apply to non-conformal antennas and more flexible techniques are required to progress the antenna and interconnect studies further. To address this challenge, this thesis investigates the utility of Spatial Warping Technique, specifically, Green Coordinates (GC), for generating arbitrary antenna and interconnect geometries. First a calibration of a straightforward application of the spatial warping techniques against a reference case of a patch antenna bent over a cylindrical surface, which can also be generated exactly, is undertaken. The thesis shows that systemic scaling distortions are introduced by the GC method and introduces a compensation method that can overcome these distortions. Subsequently, the compensated method is used to obtain new predictions of the electromagnetic performance of analyses how these complex deformations impact the performance of a flexible antenna operating in the 5-6 GHz band. with arbitrary deformations, namely, antennas bent over 2D surfaces, and with concave and convex spherical twisting or torsional deformations. Generating, full geometries is a key enabler in this thesis. The provided results for a flexible antenna operating in the 5-6 GHz band offer valuable insight to the stability of antenna performance under in-situ deformations. Finally, the new methodology is applied to characterise flexible interconnect with realistic materials condition has been investigated with concave and convex bending and an arbitrary twisting deformation. This thesis also analyses the impact of these deformations on the transmission properties of a variety of commercially available polymer and elastomer-based interconnects and compares to the performance of flat interconnects fabricated on rigid substrates. The analysis of the impact of deformations also considers the degradation in the conductivity of the printed lines due to reported mechanical deformations. The new technique introduced this thesis able to couple with an electromagnetic simulator is a promising design toolkit that can be confidently used to assess the impact of deformations on the antenna and interconnect performance and give an accurate prediction of a device under the arbitrary deformation.